2007
DOI: 10.1007/s10669-007-9019-6
|View full text |Cite
|
Sign up to set email alerts
|

Is recycled water use risky? An Urban Australian community’s perspective

Abstract: The emergence of a global water crisis has seen the necessity for a sustainable approach to water management. Policies directed towards water recycling have been implemented in many regions of the world. In Australia, prolonged drought conditions in most major cities during the past decade have led to serious national calls for less drinking water to be used (Prime Minister's Science Engineering and Innovation Council, 2003), and a strategic policy response from many State Governments, including bold targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 13 publications
6
39
1
2
Order By: Relevance
“…Community acceptance is crucial to the success of water reuse schemes [9,19]. Although generally the community is supportive of water reuse, this support declines when the end use of recycled water involves closer personal contact [3,10,19,20].…”
Section: Community Acceptance Of Stormwater Reusementioning
confidence: 99%
See 4 more Smart Citations
“…Community acceptance is crucial to the success of water reuse schemes [9,19]. Although generally the community is supportive of water reuse, this support declines when the end use of recycled water involves closer personal contact [3,10,19,20].…”
Section: Community Acceptance Of Stormwater Reusementioning
confidence: 99%
“…Although generally the community is supportive of water reuse, this support declines when the end use of recycled water involves closer personal contact [3,10,19,20]. Previous works on stormwater use indicated that there is no exception to this trend for stormwater use [21].…”
Section: Community Acceptance Of Stormwater Reusementioning
confidence: 99%
See 3 more Smart Citations